Luta por reconhecimento: uma análise intersubjetiva das histórias de vida de catadoras de materiais recicláveis - CORTEZ, Flávia Celeira (Universidade Federal do Pará, 2020)
The recycled garbage pickers as a labor category constitute a social phenomenon in the global south and expresses economic, social and environmental contradictions in the dynamics of global capitalism. In Latin America, this category is organized through the Latin American and Caribbean Network of Recyclers - RedLacre, on a national scale by the National Movement of Gabage Pickers - MNCR, and in Pará through the networks: Rede Recicla Pará, Rede CataPará and Rede CentPará, composed of several cooperatives and associations in the Metropolitan Region and interiors. Throughout the research, it is clear that the struggle for recognition is the statement that unites both the discourse of the social movement and the history of life and subjectivity of these people, the major theme on which work and life are based. Based on this perception, the aim of this research was to understand how the relationship between the dimensions of the Fighting to be Recognition proposed by Axel Honneth (2009) dialogues and makes explicit the relations of Coloniality of Power (Quijano, 2005) from the narratives of life stories of garbage pickers. The research presents in chapter 1 the contextualization of garbage pickers today within cooperatives and associations based on research carried out at the Federal University of Pará, and discusses research potentialities within this context. Chapter 2 deals with the coloniality of power from Quijano and Mignolo (2005) to understand other perspectives for interpreting the subjective and material complexities in Latin America. Chapter 3 presents the concept of Fighting to be Recognition in Honneth (2009) from the dimensions of love, law and social esteem, as concepts for analyzing the life stories of recyclable pickers from a perspective of how these statements they approach the fighting to be recognition and permeate the construction of subjectivities in coloniality.